UTANG LUAR NEGERI INDONESIA ( Perspektif Ekonomi Politik ) - Manoppo, Viviane (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2007)
The emerging of foreign debt is caused by the inability of domestic fund in financingproject which can increase national product. Foreign debt has a great potential indrowning developing countries since the aims of donor countries and recipientcountries are not always the same and perhaps even in contradictory since eachcountry has its own agenda. In fact, the issue of foreign debt in Indonesia has beenslightly felt seriously after net transfer of the capital out since 1985. Nett transferhappens if foreign debt repayment is greater than the number of new debt in eachyear. In other words, net resource transfer is getting higher.Keywords: foreign debt, developing countries,transfer